Analysis of the conditions and specifics of the border command posts engagement in the performance of missions on the restoration of control over the state border of Ukraine - Farion, Oleh; Iakubovskyi, Viktor (Social Development and Security, 2024)
Purpose: to analyze the conditions and specifics of the border command posts involvement in the performance of missions on restoration of control over the state border of Ukraine. Method: system analysis, generalization; synthesis. Findings: threats to border security, missions and measures performed by the border command post during the restoration of control over the state border of Ukraine were summarized, contradictions were identified, and the further focus of the study was formed. Theoretical implications: the result of the study allows the further development of scientific and methodological support for the involvement of bodies and units of the State Border Guard Service of Ukraine in various conditions, in particular, during the restoration of control over the state border of Ukraine. Practical implications: it is possible to use the results of the study during the organization of the operational and service activities of the state border protection bodies for a year or another period and during the implementation of measures to restore control over the state border of Ukraine. Originality: measures carried out by the border command posts during the restoration of control over the state border of Ukraine are systematized according to directions, which are aimed at ensuring the security of the state border and national security as a whole.